A critical review of TikTok’s role in motivating Indonesian students to learn foreign languages - Attruk, Muhammad Fariq Heemal; Yasin, Mohammad Ilham (MAN 4 Kota Pekanbaru, 2025)
This critical literature review examines the impact of TikTok usage on motivation and foreign language learning outcomes among students in Indonesia. Through an analysis of 26 relevant articles from reputable sources, the review reveals that TikTok has a positive effect on student engagement and foreign language acquisition, particularly in vocabulary, pronunciation, and speaking skills. The platform’s interactive short videos, diverse educational content, and the involvement of content creators are key factors contributing to its effectiveness as a learning tool. However, challenges such as potential distractions, varying content quality, and limitations in video length must be addressed. To enhance TikTok’s educational value, it is recommended that educators and content creators collaborate, providing strategic guidance to optimize learning outcomes. This study emphasizes the importance of integrating TikTok into foreign language learning in a more innovative and flexible manner.